2021
DOI: 10.1002/er.6664
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the characteristics of heat exchangers based on organic Rankine cycle system under different operating conditions

Abstract: Heat exchangers are crucial equipment, and the research related to organic Rankine cycle system is also of paramount importance. Experiments were carried out in a self-built test rig with the radial inflow turbine as the expander under three operating conditions. By analyzing UA values, the heat transfer area in different stages of evaporation or condensation was roughly calculated, so as to understand the operation performance of heat exchangers and its influence on system. Experimental results show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…11 Li et al 12 found most research focused on the improvement of the thermal efficiency and net power output of the modified ORC configurations. Lei et al 13 built an ORC system to investigate the characteristics of the evaporator and condenser under different operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…11 Li et al 12 found most research focused on the improvement of the thermal efficiency and net power output of the modified ORC configurations. Lei et al 13 built an ORC system to investigate the characteristics of the evaporator and condenser under different operating conditions.…”
Section: Introductionmentioning
confidence: 99%